Composite diaphragm, preparation method thereof and application in alkaline water electrolysis system

By using electrospinning technology on the composite separator substrate to modify polar PVA nanofibers and perform chemical crosslinking, the problems of low hydrophilicity, high contact resistance and large energy consumption in alkaline water electrolytic systems are solved, and higher energy efficiency and stability are achieved.

CN119754027APending Publication Date: 2025-04-04JIANGSU WEIDAO ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411934047.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The separators in existing alkaline water electrolysis systems have problems such as low hydrophilicity, high contact resistance and large energy consumption.

Method used

Electrospinning technology is used to modify polar PVA nanofibers on the composite diaphragm substrate and crosslink it through chemical crosslinking agent to improve the hydrophilicity of the diaphragm, thereby inhibiting bubble precipitation and reducing the contact resistance of the three-phase interface.

Benefits of technology

By improving the hydrophilicity of the diaphragm, the surface resistance of the diaphragm is reduced, bubble precipitation is suppressed, the energy efficiency of the water electrolysis system is improved, and the stability of the diaphragm is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119754027A_ABST
    Figure CN119754027A_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method of a composite membrane, a composite membrane and its application, and belongs to the technical field of composite membrane preparation. The present invention uses electrostatic spinning technology to modify polar PVA nanofibers on the composite membrane substrate, and then uses a cross-linking agent for chemical cross-linking, thereby improving the hydrophilicity of the membrane, thereby effectively inhibiting the precipitation of bubbles on the membrane surface, thereby reducing the contact resistance of the three-phase interface and improving energy efficiency. The prepared composite membrane forms a 3D layered structure, and a funnel effect is formed between the composite membrane substrate, which accelerates the transmission of the electrolyte, reduces concentration polarization, and reduces system energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite membrane preparation, and in particular to a composite membrane preparation method and application in an alkaline water electrolysis system. Background Art

[0002] Hydrogen energy, with its high energy density and green and environmentally friendly characteristics, is considered to be the most indispensable role in the development of the future energy industry. The current mainstream hydrogen production methods, such as coal-to-hydrogen and natural gas-to-hydrogen, still have emissions, so green hydrogen production will be the main hydrogen production technology in the future. Among them, large-scale water electrolysis hydrogen production technology is the most efficient means to obtain green hydrogen.

[0003] The diaphragm is one of the core materials in the alkaline water electrolysis system. The diaphragm mainly separates the positive and negative electrodes in the system, prevents the mixing of hydrogen and oxygen, and provides a transmission channel for ions. The earliest used was the asbestos diaphragm. Although it has a low cost, it has the risk of easy detachment and carcinogenicity. In recent years, the mainstream alkaline water electrolysis hydrogen production diaphragm on the market is the polyphenylene sulfide textile cloth diaphragm, which still faces the problems of low air tightness, high resistance and high energy consumption. At present, it has been proposed to use a porous composite diaphragm instead of the polyphenylene sulfide textile diaphragm, which has a low surface resistance and low energy consumption, but its performance needs to be further improved. Specifically, by improving the hydrophilicity of the diaphragm, the precipitation of bubbles on the surface of the diaphragm can be effectively inhibited, thereby reducing the contact resistance of the three-phase interface and improving energy efficiency.

[0004] PVA (polyvinyl alcohol) is a high molecular polymer with polyhydroxyl groups on the side groups, which has very good hydrophilicity. Due to its good film-forming properties, it has been widely used in water-based electrochemical energy devices. However, the swelling phenomenon of PVA is very serious. This is because the presence of polyhydroxyl groups allows it to quickly combine with water molecules in the electrolyte at the microscopic level to form hydrated ion clusters. This leads to problems such as rapid decomposition and deformation of the PVA-based film. For this reason, PVA needs to be chemically cross-linked to form a three-dimensional structure with a stable structure. Summary of the invention

[0005] In view of this, in order to solve the technical problems of low hydrophilicity, high contact resistance and high energy consumption of the existing diaphragm. In the first aspect, the present invention provides a method for preparing a composite diaphragm, by adopting electrospinning technology, polar PVA nanofiber modification is performed on the composite diaphragm substrate, and then chemical cross-linking is performed using a cross-linking agent, and by improving the hydrophilicity of the diaphragm, the precipitation of bubbles on the diaphragm surface can be effectively inhibited, thereby reducing the contact resistance of the three-phase interface and improving energy efficiency.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a composite diaphragm specifically comprises the following steps:

[0008] Step 1) dissolving PVA in an organic solvent and stirring evenly to obtain an electrospinning precursor solution;

[0009] Step 2) fixing the composite membrane substrate on a roller, and electrospinning the precursor solution in step 1) at the same time, and then performing the same operation on the other side of the composite membrane substrate to obtain a composite membrane with double-sided spraying of PVA nanofibers;

[0010] Step 3) Immersing the composite membrane obtained in step 2) in a crosslinking agent solution for crosslinking, then washing (preferably using acetone) and drying to obtain a composite membrane with PVA nanofiber surface modification.

[0011] The composite diaphragm substrate preferably adopts the polyphenylene sulfide woven cloth diaphragm or asbestos diaphragm described in the background art.

[0012] Preferably, in step 1), the mass ratio of PVA to the organic solvent is 1:1.

[0013] Preferably, in step 1), the molecular weight of PVA is 170,000.

[0014] Preferably, in step 1), the organic solvent is N-dimethylformamide (DMF) or dimethylacetamide (DMAc).

[0015] Preferably, in step 3), the cross-linking agent is selected from any one of glyoxal, glutaraldehyde, dimethylol urea and trimethylol melamine.

[0016] Preferably, in step 3), the mass concentration of the cross-linking agent is 0.01wt%-5wt%.

[0017] Preferably, in step 3), the cross-linking time is 1-3 hours.

[0018] Preferably, in the electrospinning process, the spinning voltage is 15 to 20 kV, the feed rate is 0.1 to 5 mL / h, and the distance from the spinning needle to the receiving plate is 1 to 100 cm.

[0019] On the second aspect, the present invention provides a composite diaphragm prepared by the preparation method of the above-mentioned composite diaphragm, and a 3D longitudinal layered structure formed by numerous PVA nanofibers interwoven is formed on the surface of the diaphragm. The longitudinal layered structure constitutes a rich pore distribution and exhibits a large pore-small pore-large pore structure.

[0020] In a third aspect, the present invention provides application of a composite membrane prepared by the method for preparing the composite membrane in an alkaline water electrolysis system.

[0021] Through electrospinning technology, 1D nanofiber interlaced materials can be prepared, and the fibers overlap to eventually form a dense but porous 3D layered film. The present invention uses electrospinning technology to modify polar PVA nanofibers on the composite diaphragm substrate, and then uses a cross-linking agent for chemical cross-linking. By improving the hydrophilicity of the diaphragm, the precipitation of bubbles on the diaphragm surface can be effectively inhibited, thereby reducing the contact resistance of the three-phase interface and improving energy efficiency. Compared with the prior art, it has the following beneficial effects:

[0022] (1) Polyhydroxy PVA has good hydrophilicity, which improves the poor hydrophilicity of the original composite diaphragm performance; the improved hydrophilicity reduces the diaphragm surface resistance and inhibits the bubble precipitation at the three-phase interface, thereby improving the overall energy efficiency of the water electrolysis system.

[0023] (2) Chemical cross-linking is used to ensure the stability of the 3D porous framework of PVA: the covalently cross-linked structure formed makes the PVA fibers more closely connected, effectively inhibiting the swelling of PVA and making the diaphragm more stable.

[0024] (3) The porous framework formed by overlapping PVA nanofibers cooperates with the pores of the base composite membrane to form a funnel effect. Compared with the traditional composite membrane, this method can effectively solve the problem of poor hydrophilicity caused by the surface inorganic polysulfone framework. A funnel effect is formed between the surface 3D porous framework and the composite membrane base, which accelerates the transmission of the electrolyte, reduces concentration polarization, and reduces the energy consumption of the system. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM images of the alkaline water electrolysis composite diaphragms modified with PVA nanofiber surfaces in Examples 1 to 4 are shown in Figure 1. (a) is Example 1; (b) is Example 2; (c) is Example 3; and (d) is Example 4. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0027] Example 1

[0028] This example provides a method for preparing a PVA nanofiber surface-modified alkaline water electrolysis composite diaphragm, which specifically includes the following steps:

[0029] 1) Preparation of electrospinning precursor solution: a certain amount of PVA was dissolved in 10 mL of DMF and stirred at 60° C. overnight (wherein the mass ratio of PVA:DMF=1:1) to obtain a precursor solution;

[0030] 2) Electrospinning: The composite membrane was fixed on a roller, and the electrospinning precursor solution prepared in step 1) was injected into a 10 mL syringe for spinning. The spinning process parameters were: voltage 18 kV; feed rate 0.9 mL / h; the distance from the spinning needle to the receiving plate was 12 cm. The same operation was then performed on the other side of the membrane to obtain a composite membrane with double-sided spraying of PVA nanofibers.

[0031] 3) Chemical crosslinking: The fiber membrane obtained in step 2) is immersed in an acetone solution containing glutaraldehyde (2000 mL, mass concentration 0.1 wt%) for 1 hour, and then washed with acetone and dried to obtain an alkaline water electrolysis composite diaphragm with PVA nanofiber surface modified.

[0032] Example 2 is the same as Example 1, except that the electrospinning voltage in step 2 is 20 kV;

[0033] Example 3 is the same as Example 1, except that the electrospinning voltage in step 2 is 15 kV;

[0034] Comparative Example 1 is the same as Example 1, except that the electrospinning voltage in step 2 is 10 kV;

[0035] Comparative Example 2 is the same as Example 1, except that the electrospinning voltage in step 2 is 30 kV;

[0036] Example 3 is the same as Example 1, except that the electrospinning feed rate in step 2 is 5 mL / h;

[0037] Comparative Example 3 is the same as Example 1, except that the electrospinning feed rate in step 2 is 8 mL / h;

[0038] Example 4 is the same as Example 1, except that the mass concentration of the chemical cross-linking solution in step 3 is 5wt%;

[0039] Comparative Example 4 is the same as Example 1, except that no chemical crosslinking is performed, that is, the mass concentration of the chemical crosslinking solution in step 3 is 0 wt %;

[0040] Test Example 1

[0041] The surface and cross-section of the composite membrane obtained in Examples 1-4 were observed using SEM. Figure 1 As shown. Under low magnification, the base membrane shows a 3D layered morphology formed by numerous PVA interweaving. At the same time, from the cross-section of the composite membrane, it can be observed that the surface PVA thin layer forms an obvious longitudinal layered structure. Due to the hydrophilicity of PVA, coupled with the top-down macropore-small pore-macropore structure, a funnel effect is formed, which can significantly improve the transmission efficiency of the electrolyte.

[0042] Test Example 2

[0043] In this test, the alkali absorption rate, surface resistance, porosity, bubble point pressure, water contact angle and wetting time of the diaphragms in the above-mentioned Examples 1-4 and Comparative Examples 1-4 were measured. The measurement results are shown in Table 1.

[0044] The average pore size can reflect the pore size of the diaphragm, which is of great significance to the OH-permeability and gas barrier performance of the diaphragm. The test method refers to GBT 21650.1-2008 "Determination of pore size distribution and porosity of solid materials by mercury injection and gas adsorption".

[0045] The surface resistance of the diaphragm has an important influence on the conductivity of the diaphragm. The surface resistance refers to the resistance value per unit area of ​​the diaphragm, which indicates the resistance of current passing through the diaphragm. The lower the surface resistance, the smaller the resistance value per unit area, and the smaller the resistance when current passes through the diaphragm. The test method refers to SJT10171.5-1991 "Test Method for Performance of Alkaline Battery Diaphragm".

[0046] The alkali absorption rate is directly related to the conductivity of the diaphragm. A larger porosity means a larger electrolyte flux and a smaller surface resistance of the diaphragm. In this test example, the composite diaphragms prepared in the above examples were cut into 2cm*2cm squares, the dry weight was measured, and then they were immersed in 30% KOH for 12h; then the alkali absorption rate of the composite diaphragm was calculated by measuring the mass and volume difference between the dry film and the wet film before and after alkali absorption.

[0047] Bubble point pressure refers to the pressure at which the gas in the diaphragm begins to penetrate at a certain temperature. A higher bubble point pressure indicates that the diaphragm has better gas barrier properties and can more effectively prevent gas penetration. The test method refers to GB / T26204-2010 "Performance Test Method of Liquid Phase Filter Materials - Air Bubble Point Test".

[0048] The water contact angle can reflect the wetting properties of the film. The test method refers to GB / T 30693-2014 "Measurement of the contact angle of plastic film with water". The wetting time is the time difference from when the water droplet contacts the diaphragm and begins to generate a contact angle until the contact angle reaches 0.

[0049] Table 1 is a comparison of the surface resistance, alkali absorption rate, bubble point pressure and water contact angle data in Examples 1-4 and Comparative Examples 1-4.

[0050]

[0051]

[0052] After PVA modification, the alkali absorption rate is ≥80% and the bubble point pressure is ≥2 bar, indicating that this strategy can effectively fill the macropores locally, making the diaphragm have better gas barrier properties. Due to the polyhydroxy structure of PVA fibers, the diaphragm has good hydrophilicity, and the water contact angle of all diaphragms modified with PVA fibers is ≤50°. This super hydrophilicity greatly improves the performance of the diaphragm in the water electrolysis process and reduces the energy consumption of the system.

[0053] The above are only preferred specific implementations of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a composite diaphragm, characterized in that: The specific steps include: Step 1) dissolving PVA in an organic solvent and stirring evenly to obtain an electrospinning precursor solution; Step 2) fixing the composite membrane substrate on a roller, and electrospinning the precursor solution in step 1) at the same time, and then performing the same operation on the other side of the composite membrane substrate to obtain a composite membrane with double-sided spraying of PVA nanofibers; Step 3) The composite membrane obtained in step 2) is immersed in a crosslinking agent solution for crosslinking, and then washed and dried to obtain a composite membrane with PVA nanofiber surface modification.

2. The method for preparing a composite diaphragm according to claim 1, characterized in that: In step 1), the mass ratio of PVA to the organic solvent is 1:

1.

3. The method for preparing a composite diaphragm according to claim 1, characterized in that: In step 1), the molecular weight of PVA is 170,000.

4. The method for preparing a composite diaphragm according to claim 1, characterized in that: In step 1), the organic solvent is N-dimethylformamide (DMF) or dimethylacetamide (DMAc).

5. The method for preparing a composite diaphragm according to claim 1, characterized in that: In step 3), the cross-linking agent is selected from any one of glyoxal, glutaraldehyde, dimethylol urea and trimethylol melamine.

6. The method for preparing a composite diaphragm according to claim 1, characterized in that: In step 3), the mass concentration of the cross-linking agent is 0.01wt%-5wt%.

7. The method for preparing a composite diaphragm according to claim 1, characterized in that: In step 3), the cross-linking time is 1-3 hours.

8. A method for preparing a composite diaphragm according to any one of claims 1 to 7, characterized in that: In the electrospinning process, the spinning voltage is 15 to 20 kV, the feed rate is 0.1 to 5 mL / h, and the distance from the spinning needle to the receiving plate is 1 to 100 cm.

9. A composite diaphragm prepared by the method for preparing a composite diaphragm according to any one of claims 1 to 8, characterized in that: A 3D longitudinal layered structure composed of numerous PVA nanofibers interwoven is formed on the surface of the diaphragm. The longitudinal layered structure constitutes a rich pore distribution and exhibits a large pore-small pore-large pore structure.

10. Use of the composite diaphragm prepared by the method for preparing a composite diaphragm according to any one of claims 1 to 8 in an alkaline water electrolysis system.